Guided Analysis of Legal Judgments by Means of Collaborative Learning: A Strategy to Develop Juridic Reasoning - Baltodano Mayorga, Jose Daniel (2023)
This paper documents the results of implementing a guided analysis of judgments as a collaborative learning strategy in the Legal Reasoning II course at the University of Costa Rica, Liberia campus during the second semester of 2021. To develop a critical and contextualized perspective on the legal phenomenon, a qualitative assessment of this tactic was conducted in order to enhance learning about the elements for legal interpretation and argumentation through peer work. It is concluded that peer collaboration impacted the learning process positively. This strategy promotes a comprehensive approach, integrating theory, practice, and context for a significant construction of knowledge. In addition, it develops multiple abilities and attitudes related to the content being discussed as well as research skills and ongoing learning, among others. Thus, this strategy proved to be ideal to foster active and critical learning of legal reasoning.